Pemanfaatan Media Pembelajaran Alat Peraga Sistem Kardivaskulas untuk Menaikkan Hasil Belajar SD/MI - Haiati, Siti Zikna Al; Prayogo, Muhammad Suwignyo (Lembaga Yasin AlSys, 2023)
This researcch was conducted to find out about the impact of using visual aids on understanding the material of the circulatory system. The cardiovascular system is a material in science learning that includes organs that are used during the transportation process, blood circulation processes, abnormalities in blood circulation and circulatory diseases that should be understood. But of course there are obstacles in the learning process both the lack of understanding of students in capturing learning material, that way the teacher can use learning media such as teaching aids, the use of teaching aids that image the necessary work operations needed to visualize in memory, so the direction of this research is to test the success of the circulatory system visual media in the teaching and learning process. As well as helping teachers to make it easier when doing learning and easily understood by students.